Effect of Self-Care Program on the Quality of Life in Sickle Cell Anemia - Gholam Reza Mahmodi; Sadigeh Fayazi; Simin Jahani; Bizhan Kaykhaei; Seyed Mahmod Latifi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background & Objective: sickle cell anemia, a chronic disease, which has many complication affects patient’s. This quality of life’s. Therefor, they need caring to maintain their life. The goal of this study was investigating the effect of self care plan on the quality of life’s sickle cell anemia.Subjects and Methods: This study was a clinical trial research carried out on 70 sickle cell anemics and allocated in two groups randomly. The instruments of data collection were demographic, assessment educational needs and SF-36 quality of life questionnaire. One educational session of self care (60 minute) was implemented for the experimental group. The patients’ quality of life was measured in two times (before and three months past intervention). Results: T-test showed that the total scores of quality of life’s two groups have not significant difference before intervention) p=0.58), but the difference was significant between two groups in after intervention (p<0.001). PAIR T-TEST showed that the total scores of patients’ quality of life in before and after intervention have significant difference in the control group and the quality of life has decreased in this group (p=0.019(,but this difference was not significant in experimental group and quality of life has remained in this group )p=0.91(.Conclusion: Reduced quality of life of control group and stable quality of life of experimental group indicate that the self care program improve the quality of life of these patients. Designing program based on patient educational needs, capabilities and cooperation can have a positive influence on the patients’ quality of life of patient make to achieve results positive.